2021
DOI: 10.1126/science.abg5332
|View full text |Cite
|
Sign up to set email alerts
|

Origins and evolution of extreme life span in Pacific Ocean rockfishes

Abstract: A fishy tale of long and short life span Fish have wide variations in life span even within closely related species. One such example are the rockfish species found along North Pacific coasts, which have life spans ranging from 11 to more than 200 years. Kolora et al . sequenced and performed a genomic analysis of 88 rockfish species, including long-read sequencing of the genomes of six species (see the Perspective by Lu et al .). From this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 79 publications
9
66
0
Order By: Relevance
“…In agreement with our findings, other authors reported that high levels of the AKT1 isoform could be related with the loss of BRCA1 expression and HR inhibition in breast cancer models, suggesting that a similar mechanism could be possible in HGSOC [ 23 , 24 ]. Furthermore, AKT1 has been identified as an age-associated gene in different non-human species, thanks to its ability to stimulate the insulin/IGF1 pathway and inhibit DNA repair mechanisms [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, other authors reported that high levels of the AKT1 isoform could be related with the loss of BRCA1 expression and HR inhibition in breast cancer models, suggesting that a similar mechanism could be possible in HGSOC [ 23 , 24 ]. Furthermore, AKT1 has been identified as an age-associated gene in different non-human species, thanks to its ability to stimulate the insulin/IGF1 pathway and inhibit DNA repair mechanisms [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kolora et al (2021) found an expansion in the immune modulatory butyrophilin gene family in long-lived rockfishes compared to short-lived rockfishes. A similar number of genes in most immune pathways (60%, 12 in 20 pathways, Table S10) were detected both in the three short-lived fish species (T. fasciatus, N.…”
Section: Expansion and Contraction Of The Roughskin Sculpin Genomementioning
confidence: 95%
“…The lifespans of vertebrates are highly variable, which range from a few weeks to several hundred years in nature (Kolora et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in sequencing technologies along with falling sequencing costs have made it increasingly feasible to sequence and assemble reference genomes for non-model species (Feng et al, 2020; Kolora et al, 2021; Hotaling et al, 2021; Formenti et al, 2022; Rhie et al, 2021). Non-model reference genomes can then be used to assemble short reads from reduced-representation or whole genome sequencing into shared loci across individuals, and an increasing number of studies use a reference genome of a focal study taxon for assembly.…”
mentioning
confidence: 99%